Kajian Komitmen K3 Bidang Organisasi, SDM dan Anggaran K3 di PT X Berdasarkan Permenaker Nomor Per-05/Men/1996 - Bambang Aminarto; Baju Widjasena; Sutopo Patria Djati (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2011)
HSE Management System in Indonesia refer to Labor Minister Number Per-05/Men/1996 on Safety Management System and Occupational Heath. The main thing in implementing the HSE Management System the main thing is the commitment of companies towards HSE Management System itself. This study aims to formulate strategies to strengthen management’s HSE commitment on PT X. the approach used in this research is a qualitative approach. As a research subject is the management of the Head Office of PT X, located in Bandung. Retrieving data trough Focus Group Discussion and in-depth interviews. Focus Group Discussion conducted by the number of participants by 14 people while in-depth interviews conducted on the leaders and HSE headquarters staff PT X. The results show that commitment in the implementation of HSE in PT X already exists but its implementation is not optimal. HSE organization that is in PT X has not been biased because the organization takes a strategic policy level is still sub-section, in addition to the human resources that deal with HSE is not in accordance with educational backgrounds that are less than optimal.